Pengaruh Kepercayaan Merek Telkomsel dan Kepuasan Konsumen Terhadap Loyalitas pada Mahasiswa STIS Al-Hilal Sigli - T. Sabirin (HEI EMA : Jurnal Riset Hukum, Ekonomi Islam, Ekonomi, Manajemen dan Akuntansi, 2022)
The purpose of this study was to examine the effect of Telkomsel brand trust and consumer satisfaction on student loyalty at STIS Al-Hilal Sigli. The data analysis method in this study uses multiple linear regression to predict the effect of the independent variables. The population in this study were students of STIS Al-Hilal Sigli and who used Telkomsel services from 2017 to 2021, with a sample of 80 respondents. The results showed that brand trust had a significant effect on loyalty. It can be interpreted that trust has a direct effect on loyalty. That is, this finding is similar to several previous studies that consumer trust has an effect on consumer satisfaction and loyalty. consumer goals have a significant effect on loyalty, this shows that satisfied customers make repurchases so that long profits for the company.